Análise sistemática de problemas patológicos em estruturas de concreto armado em ambiente Windows - Renato Martins Grossi (1996)
The aim of this work was to develop a software in the field of Structure Patology to Analyse Reinforced Concrete Structures, at Windows environment, enabling the user to interact with the software in the search of the pathognomy of the structures in analysis. This will be possible due an elaborated research system arranged by means of pictures, photographs, texts, graphics, etc - in wich the user give the data, obseved or know, interacting with the program asnwering multiple answer questions. The Structural pathologies are manifested by a group of sings - as deformations, fissures, reinforced concrete colour changes, expansions, cracks, exfolation, etc - making the diagnosis, of the pathologies, difficult and intrincated. This software is a counterpart to these adjectives, besides being considered also a inedited dissertation work, in this subject, at the master degree course in Structure Engeniering of E.E.U.F.M.G2. The role of this program at Windows environment is based also in the creation of a better understtanding and knowledge of the subject, Patology in Reinforced Concrete Structures, in comparison with the traditional analysis means.